MOSFET drain current noise modeling with effective gate overdrive and junction noise - Chan, L. H. K. (2013)
In this letter, a drain current noise model that includes the channel thermal noise and the shot noise generated at the source-bulk junction and the drain-bulk junction is presented. A unified analytical expression is derived to ensure excellent continuity with smooth transition of drain current noise from weak- to strong-inversion regimes, including the moderate-inversion region. Excellent agreement between simulated and extracted noise data has shown that the proposed model is accurate over different dimensions and operating conditions.